Combination of Diane-35 and Cangfu Daotan Wan Effectively Ameliorates Inflammatory Response, Stress State, and Hormone Levels in Patients with Polycystic Ovary Syndrome (PCOS), Leading to Significant Improvement in Clinical Treatment Outcomes - Chen L; Fang CP; Chen Y; Gu WH; Wang SL; Niu N; Zhang QH (International Journal of Women's Health)
Li Chen,1,* Cai-Ping Fang,1,* Yan Chen,1 Wei-Hua Gu,1 Sai-Li Wang,1 Ning Niu,1 Qin-Hua Zhang2 1Department of Gynecology, Taizhou Hospital of Traditional Chinese Medicine, Taizhou, People’s Republic of China; 2Department of Gynecology, Shanghai Shuguang Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qin-Hua Zhang, Email bzie564@163.comObjective: To assess the impact of combining Diane-35 with Cangfu Daotan Wan on inflammatory response, stress response, and hormone levels in patients with polycystic ovary syndrome (PCOS), and to offer insights for clinical management.Methods: A retrospective analysis was conducted from January 2022 to March 2024, encompassing PCOS patients treated at our hospital who fulfilled the inclusion criteria. Patients were categorized into two groups: the study group receiving Diane-35 plus Cangfu Daotan Wan, and the control group receiving Diane-35 alone. Comparisons were made between the two groups regarding inflammatory markers, stress response indicators, hormone levels, and overall treatment efficacy.Results: Post-treatment, the study group exhibited a lower incidence of polycystic ovarian changes and a higher overall efficacy rate compared to the control group (P< 0.05). Inflammatory factors IL-6, TNF-α, and MCP-1 were significantly reduced in the study group versus the control group (P< 0.05). Oxidative stress markers SOD and GSH were significantly elevated, while GSS was significantly decreased in the study group compared to the control group (P< 0.05). No significant differences were observed in FSH, LH, LH/FSH ratio, or testosterone levels between the two groups (P> 0.05). The BMI index was significantly lower in the study group than in the control group (P< 0.05). Additionally, traditional Chinese medicine symptom scores were significantly reduced in the study group compared to the control group (P< 0.05).Conclusion: The combination of Diane-35 and Cangfu Daotan Wan effectively ameliorates inflammatory response and stress state, modulates hormone levels, and enhances clinical treatment outcomes in PCOS patients. This combined therapy is both safe and efficacious, warranting further application in clinical practice.Keywords: polycystic ovary syndrome, Diane-35, Cangfu Daotan Wan, inflammatory response, stress response, hormone levels